ARTIFICIAL INTELLIGENCE IN LANGUAGE TEACHING - GULBOYEV, Abdulla Xayrulla o`g`li (The Lingua Spectrum, 2025)
This article discusses the impact of artificial intelligence (AI) on the language teaching process, its advantages, areas of application, and its role in increasing the efficiency of the educational process. The role of AI-based platforms, mobile applications, automated assessment systems, and adaptive learning technologies in modern language teaching is analyzed.